The Responsiveness of Households to Energy Demand Management Initiatives: Segmenting by Household Types. Issue 4 (1st October 2016) - Kleinschafer, Jodie; Morrison, Mark
ABSTRACT: Segmentation is often a complex and costly process, which commonly involves identifying groups with differing attitudes and behaviors or demographics. However, the segments generated may not adequately explain differences between consumers, or it can be difficult to identify households for target marketing, which consequently makes it difficult to use segmentation in practice. In this paper we present segmentation by household type as a simple method of segmentation, accessible to nonprofit organizations with limited resources and able to be employed using a secondary data set or with relatively simple data collection and analysis. Despite its simplicity, our findings show that this form of segmentation differentiates well between segments in terms of their actual electricity use, their past efficiency behaviors and preferences for efficiency programs. The results of focus groups and a survey of 4, 000 households reveal, among other things, the effect of having children and of marital status on energy use and efficiency behaviors, the high curtailment but low investment behaviors of single parent households, and the low efficiency behaviors of shared households.